Analysis of the Exchange Rate of the Rupiah Against the US Dollar and the Factors that Influence it - Kurniawan S., Amri Darma; Rizki, Rizki; Rusiadi, Rusiadi; Nasution, Lia Nazliana (LPPM UIKA Bogor, 2024)
This research aims to determine the effect of the Fed Interest Rate, Foreign Exchange Reserves and Antam Gold Prices on the USD/IDR Exchange Rate. Research data using secondary data obtained from the Bank Indonesia website, Trading Economics and Gold Prices.org with a time span of 2013 to 2023. The research uses the Multiple Linear Regression method (Ordinary Least Square) using Eviews 12 software. The results of Data Analysis based on the Simultaneous Test (F-Test) showed that the Fed Interest Rate, Foreign Exchange Reserves and Antam Gold Prices simultaneously had a significant effect on the USD/IDR Exchange Rate. Based on the results of the Regression Model Interpretation, only the Foreign Exchange Reserve variable has an unidirectional relationship with the USD/IDR Exchange Rate so that it can appreciate the Rupiah Exchange Rate with the US Dollar if the Foreign Exchange Reserve Value maintained by Bank Indonesia is added or increased. Based on the regression results, the contribution of the influence of the Independent Variable on the Dependent Variable is 86.41%. The remaining 13.59% is influenced by other variables not included in this research.